Program ‘Aisyiyah Dalam Mewujudkan Keluarga Sakinah Menuju Islam Berkemajuan - Samsidar .; Darliana Sormin (UMSU, 2019)
In challenging complex dynamics and challenges, ‘Aisyiyah must change direction which starts from changing her own destiny and simultaneously changes direction towards enlightenment. One of the questions and strategic issues of a national nature is the family debate. One of the programs Aisyiyah, the decision of the 47th Congress in 2015, one century ‘Aisyiyah in Makassar is about a program in the field of family development towards a sakinah family. The Sakinah family has a sense of peace, security and peace. The family must be able to reflect the ideal society, namely a society that is progressive, empowered and happy physically and mentally. Produced from these sakinah families, a progressive, empowered and physically happy community will be realized. In order for the community to achieve the title of progress, empowerment and happiness to be born and mentally, some conditions are needed, among others, presenting piety to Allah SWT, can develop a just nature based on Islamic values and free from economic imbalances and social inequality.